The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1158/1078-0432.ccr-17-3420
|View full text |Cite
|
Sign up to set email alerts
|

A Coclinical Radiogenomic Validation Study: Conserved Magnetic Resonance Radiomic Appearance of Periostin-Expressing Glioblastoma in Patients and Xenograft Models

Abstract: Radiomics is the extraction of multidimensional imaging features, which when correlated with genomics, is termed radiogenomics. However, radiogenomic biological validation is not sufficiently described in the literature. We seek to establish causality between differential gene expression status and MRI-extracted radiomic-features in glioblastoma. Radiogenomic predictions and validation were done using the Cancer Genome Atlas and Repository of Molecular Brain Neoplasia Data glioblastoma patients ( = 93) and ort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 48 publications
3
56
0
Order By: Relevance
“…Indeed, the translational relevance of pre-clinical radiomic ‘discovery’ studies in animal models is now becoming evident. For example, Zinn et al recently employed radiomic analyses on glioblastoma magnetic resonance data sets from mice and humans, and showed that selected imaging features are conserved across species [ 44 ]. In the current context, future work employing CT scan data from large scale population-based CRC PDX trials is now warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the translational relevance of pre-clinical radiomic ‘discovery’ studies in animal models is now becoming evident. For example, Zinn et al recently employed radiomic analyses on glioblastoma magnetic resonance data sets from mice and humans, and showed that selected imaging features are conserved across species [ 44 ]. In the current context, future work employing CT scan data from large scale population-based CRC PDX trials is now warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The variability generated by different voxel sizes can also be reduced by spatial resampling 9 , 11 , 12 . Moreover, brain extraction is mandatory to remove the skull regions that generate the most important variations in intensities and to define the region in which intensities should be considered before any image intensity normalization 13 , 14 . However, even though these three types of pre-processing of brain MRI are widely accepted by the community, there is no consensus within radiomics studies regarding the applied image normalization method (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have predicted prognosis using features obtained from functional imaging ( Ryu et al, 2014 ; Lee et al, 2016 ). Recently, radiomics has been combined with genomics to leverage two distinct types of information to better study various tumor types ( Gutman et al, 2015 ; Li et al, 2016 ; Beig et al, 2018 ; Zinn et al, 2018 ). The new approach is referred to as radiogenomics and has to potential to reveal novel findings combining two distinct high dimensional information of gene and imaging information.…”
Section: Introductionmentioning
confidence: 99%